APLIKASI JEJARING SOSIAL RELAWAN SIAGA ONLINE BERBASIS LOKASI - Rini Nuraini Sukmana; Ilham Muttaqien; Mira Sylvia Kasegrina Siregar (LPPM STMIK BANDUNG, 2015)
Human resources in an organization is a valuable asset, especially with the number of human resources should bemanaged. Good human resource management will certainly affect on the existence and quality of the organizationas well as the Standby Volunteer who had a lot of volunteers scattered throughout Indonesia, have major problemsfaced in conducting data management volunteers and sympathizers. Volunteers standby as a community of youngpeople who will focus on the actions of disaster preparedness and variety of social action community in anyactivities can not be separated from the role of the volunteers and supporters in each run humanitarian taskundertaken, to support the management and human resources development Volunteer Alert needed a volunteermanagement system that is proportionate to manage it. One way is to develop an application that combines theconcept of volunteer computerized data collection with the concept of location-based social networking website inone application. The method developed is to modify the function of HTML5 Geolocation API to determine thepoints volunteer locations on the map. In this thesis research has built a Social Network Application LocationBased Online Volunteer Alert obtained results that the application is expected data management andimplementation of activities Volunteer Alert can be implemented properly and effectively. Keywords : applications, database, social network, volunteer alert, location-based services, html5 geolocationapi.